2008
DOI: 10.1510/icvts.2007.172569
|View full text |Cite
|
Sign up to set email alerts
|

Non-harvestable radial artery. A bilateral problem?

Abstract: Since radial artery is preferably harvested from a non-dominant hand, our aim was to study whether there are contraindications for radial artery harvest in the dominant hand if the radial artery of the other hand is not suitable for harvesting. Thirty-three patients scheduled to coronary artery bypass grafting with contraindication for radial artery harvest in the non-dominant hand underwent Allen test, upper arm Doppler ultrasonography and digital pletysmography. In ultrasonography, both anatomical and circul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
8
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 8 publications
0
8
0
Order By: Relevance
“…Nevertheless, the specificity of the clinical Allen test remains high in these conditions, ranging from 91% to 97.1%, 6,12,13 whereas some authors found the sensitivity was as low as 54.5%. 13 A specificity of 91% can be too low in the context of a decision-making process when applied to the prediction of the outcome of an aggressive procedure in single patients, but it is already quite high when the information is used as an epidemiologic marker for group comparisons.…”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations
“…Nevertheless, the specificity of the clinical Allen test remains high in these conditions, ranging from 91% to 97.1%, 6,12,13 whereas some authors found the sensitivity was as low as 54.5%. 13 A specificity of 91% can be too low in the context of a decision-making process when applied to the prediction of the outcome of an aggressive procedure in single patients, but it is already quite high when the information is used as an epidemiologic marker for group comparisons.…”
Section: Discussionmentioning
confidence: 96%
“…[3][4][5][6][7][11][12][13][14][15] However, the sensitivity and specificity of the Allen test for the occlusion of the ulnar artery was quite high, at 95% and 100%, respectively, for Hirai et al 21 compared with arteriography in 192 hands, and was 96% and 97%, respectively, for Pistorius et al 8 in a series of 576 patients with Raynaud phenomenon with a plethysmographic test as reference.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…The modified AT has also been validated by Ruengsakulrach and colleagues 7 using a 10-s cutoff, similar to that used in our series. Glavin and Jones 8 and Kohonen and colleagues 9 confirmed the safety and efficacy of the modified AT and failed to establish any benefit of Doppler USG in assessing the adequacy of collateral flow in the hand. Although postoperative hand ischemia has been reported when the AT alone was used to assess collateral circulation in the hand, 10 complications have occurred even after USG examination, 11 which therefore does not provide 100% safety.…”
Section: Discussionmentioning
confidence: 99%
“…When there is a contraindication for radial artery harvest in the non-dominant hand, the risk of having a non-harvestable artery in the dominant hand is doubled. 28 Patients with hand ischemia after radial artery harvest can present with a variety of symptoms ranging from hand fatigue, to resting pain and gangrene. Severe ischemia has been reported to develop in up to 0.03%, whereas mild ischemia may develop in up to 10%.…”
Section: Contraindications To Radial Artery Harvestingmentioning
confidence: 99%